Alterações na difusão do monóxido de carbono e teste de caminhada em vítimas de inalação de fumaça após incêndio em casa noturna - Susin, Cíntia Franceschini (2015)
The inhalation lesion is one of the biggest mortality causes in fire exposed patients at closed places. Medium and long follow-up respiratory consequences are still rarely reported at world literature. Alveolar-capillary membrane commitment caused by inhaled particles can persist during several years and progress to bronchiolitis obliterans. Thereby, the objective of this work was to evaluate the Diffusing Capacity for Carbon Monoxide (DLCO) lung test, at patients that inhaled toxic smoke at a fire in the nightclub Kiss at January 2013, in Santa Maria, parallel 29°, south Brazil, after first year follow-up. Were included 64 patients that were submited to DLCO and 6-minutes Walk Test (WT6) measurements. Dates were obtained by standard formularies including demographic characteristics, respiratory symptoms and inhalatory medication use. DLCO average was 63% (20,95 mL/mmHg/min) from predict and WT6 distance was 505,55 meters. At studied sample, 21,8% were asthmatics and when compared to no-asthmatics, they had better DLCO (p = 0,017). There was no statistical significance when compared other variables how: tracheal intubation, dyspnea, tabagism, dessaturation at WT6, smoke exposure time and intubation duration to DLCO results. Studied patients had a DLCO reduction greater than current literature. Development of chronic pulmonary complications, especially bronchiolitis obliterans, is a concrete possibility and must be better clarified and adequate screened. Late development of this kind of complication makes a prolonged ambulatorial follow-up indispensable.